2022
DOI: 10.3390/coatings12121992
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Annealing on the Microstructure and Mechanical Properties of Ni-W/Boron Composite Coatings

Abstract: Ni-W/boron composite coatings are deposited from an ammonia citrate bath with a boron particle suspension. The effect of the boron incorporation into the Ni-W alloy coating and subsequent heat treatment of the deposits on the microstructure and properties of the Ni-W/boron coatings have been investigated. The boron particles can be uniformly dispersed in the Ni-W alloy, which can lead to an enhancement in the wear performance and hardness of the coatings. The XRD results show that a new Ni4W phase can be forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In our previous work, we reported that the original Ni-W alloy coatings and composite Ni-W coatings modified by adding amorphous boron particles (Ni-W/B) can be successfully deposited on carbon steel using the electrodeposition method [4,23,24]. The hardness and wear resistance of the coatings are significantly improved via the incorporation of an appropriate content of amorphous boron particles because these particles uniformly distribute and provide a smooth surface [4,23].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we reported that the original Ni-W alloy coatings and composite Ni-W coatings modified by adding amorphous boron particles (Ni-W/B) can be successfully deposited on carbon steel using the electrodeposition method [4,23,24]. The hardness and wear resistance of the coatings are significantly improved via the incorporation of an appropriate content of amorphous boron particles because these particles uniformly distribute and provide a smooth surface [4,23].…”
Section: Introductionmentioning
confidence: 99%